Changes in the Work Process from ISO 9001 Certification at a Health Sector Organization - Miranda, Adílio Renê Almeida; Almeida, Elizangela Gomes (Revista Gestão da Produção Operações e Sistemas, 2007)
This study was carried out an ISO 9001 certified company in the health sector, located in Minas Gerais. Theobjective was to identify the organizational changes in the work process resulting from certification. By means ofqualitative research, participative observation and document research, it was possible to ascertain a reorganizationof the work system, with changes seen in the following areas: personnel, work, information and technology.Furthermore, it was also ascertained that the implemented quality management system is a tool that essentiallycontrols the work.Key words: Quality management; Change; Work process